Virtual Socialization Through Online Game: Social Interaction in Roblox - Syakilah Azzahra; Najwa Naela Putri; Asyrof Bahauddin Mubarok; Khomarudin Khomarudin (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2025)
Online games, especially on the Roblox platform, have become an increasingly significant digital interaction environment. This study aims to explore social interactions in the context of online gaming, with a particular focus on the Roblox platform. Roblox was chosen as the research subject due to its growing popularity and the diverse and complex social environment it offers. A qualitative approach was employed, with data collected through direct observation within the game, allowing for firsthand observation of player interaction dynamics. Additionally, a sample of Roblox players was surveyed using a questionnaire containing several questions related to interaction and socialization. The collected data were then analyzed by identifying key themes related to the game's influence on friendship-building, collaboration, and emerging communication norms within the gaming community. As a result, player interactions in the online gaming environment have implications for creating inclusive online communities and designing games that enhance players' social experiences. Keywords: Social interaction, Online gaming, Roblox